Specific relations of visual skills and executive functions in elite soccer players - Knöllner, Antonia; Memmert, Daniel; von Lehe, Marec; Jungilligens, Johannes; Scharfen, Hans-Erik (Frontiers in Psychology, 2022)
Visual and cognitive skills are key to successful functioning in highly demanding settings such as elite sports. However, their mutual influence and interdependencies are not sufficiently understood yet. This cross-sectional study examined in a cross-sectional study design the relationship of between visual skills and executive functions in elite soccer players. Fifty-nine male elite soccer players (age: 18-34 years) performed tests assessing visual clarity (left-, right- and both eyes), contrast sensitivity, near-far quickness, and hand-eye coordination. Executive functions measures included working memory capacity, cognitive flexibility, inhibition and selective attention. Overall, visual abilities were largely correlated with the executive functions. Near-far quickness performance showed a large correlation with an executive function total score as well as with cognitive flexibility, working memory, and especially selective attention. Visual clarity and contrast sensitivity were moderately correlated with the cognition total score. Most consistent correlations of the executive functionswith the visual functions were present for working memory. , specifically with the visual clarity of the right- and both eyes and near-far quickness. These findings present an overall vision-cognition relationship but also very specific linkages among subcategories of these functions, especially by indicating meaningful relations between near-far quickness, selective attention and cognitive flexibility. Further studies are needed to investigate the neuropsychological mechanisms accounting for the correlations and possible improvements of the executive functions by training specific visual skills.